2015
DOI: 10.3310/phr03050
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers in the Playground: a pilot cluster randomised controlled trial of a physical activity intervention for children aged 18 months to 4 years

Abstract: BackgroundThe preschool years are considered critical for establishing healthy lifestyle behaviours such as physical activity. Levels of physical activity track through childhood into adulthood and establishing habitual physical activity early in life is therefore vital. Time spent outdoors is associated with greater physical activity and playground interventions have been shown to increase physical activity in school-aged children. There are few preschool, playground-based interventions and these have given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 137 publications
(246 reference statements)
1
23
0
Order By: Relevance
“…Similar to other studies, ECE providers expressed generally positive opinions about the acceptability and feasibility of the intervention [40][41][42]. This study extended the work of others by seeking parents' opinions which, interestingly, were less favorable than ECE providers' opinions.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to other studies, ECE providers expressed generally positive opinions about the acceptability and feasibility of the intervention [40][41][42]. This study extended the work of others by seeking parents' opinions which, interestingly, were less favorable than ECE providers' opinions.…”
Section: Discussionsupporting
confidence: 77%
“…Use of cut-points derived from American preschoolers to assess PA in a British population may not fully capture the PA behavior of children, due to the different social and economic environments in which PA takes place in the U.S. compared to the U.K. Conversely, other research has reported that 95.6% of British preschoolers completed TPA recommendations for health. Similar to the aforementioned studies by O’Dwyer et al [ 8 , 12 , 13 ], Barber et al [ 15 ] used cut points which were validated in American preschoolers [ 16 ] despite investigating children from Bradford [ 15 ]. Preschool-based approaches that decrease sedentary behavior and increase PA may aid in combating the epidemic of juvenile obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Playgrounds are a conducive means for child development with respect to physical, intellectual, emotional, and social processes (Hughes 1995). Recent developments foreground playgrounds as an intervention to promote child health (Barber et al 2015). Studies also deal with safety in playgrounds, such as injury cases (Ball 2002), and ergonomic structures that need to adjust for children's needs given increased urbanization (Nowakowski and Charytonowicz 2007).…”
Section: I T E R At U R E O N P L Ay S Pa C E S a N D T H E R E G U L At I O N O F C H I L D R E N ' S A C T I V I T I E S Pl Aygrounds Imentioning
confidence: 99%
“…This user of public playgrounds did not opt to completely prohibit her children from playing there. 23 21 Such playgrounds are considered insufficient for further cognitive and physical development of children since their designs prioritize safety over challenging children's abilities and promoting learning (Barber et al 2015).…”
Section: The Fallout: Social Reproduction Of Childhood Inequalit Ymentioning
confidence: 99%
See 1 more Smart Citation